Services-led industrialization in India: Prospects and challenges - Nirvikar Singh (University of California, Economics Department, 2006)
This paper provides an integrated analysis of the role of the service sector in recent Indian economic development. It discusses the nature of services, their distinction from products, and their categorization. It provides an overview of India's overall growth experience, and a detailed examination of the contribution of the service sector to growth. It includes an examination of the potential for spillovers from IT, ITES and other service sectors such as financial services, to the rest of the economy, drawing on econometric work, as well as input-output analysis of linkages to understand these possible spillovers and growth potentials. Based on this evidence, it appears that India's manufacturing sector development may have been constrained in part by weaknesses in key service sectors such as transportation and electricity. The paper also considers the particular role of international trade in services, which is of growing importance. It discusses the consequences for employment of different growth paths, the challenges of education and manpower training to support and sustain India's development path, and social and environmental issues, including regional inequality issues. The Indian experience is related to recent discussions of industrial policy, and development policy more generally.
Keywords: 330; Wirtschaftswachstum; Dienstleistungssektor; Internationaler Dienstleistungsverkehr; Indien; IKT-Sektor